Usable usability : simple steps for making stuff better - Reiss, Eric L., 1954- (John Wiley & Sons, 2012)
"The A-to-Z guide to spotting and fixing usability problems. Frustrated by pop-ups? Forms that make you start over if you miss a field? Nonsensical error messages? You're not alone! This book helps you simply get it right the first time (or fix what's broken). Boasting a full-color interior packed with design and layout examples, this book teaches you how to understand a user's needs, divulges techniques for exceeding a user's expectations, and provides a host of hard won advice for improving the overall quality of a user's experience. World-renowned UX guru Eric Reiss shares his knowledge from decades of experience making products useable for everyone ... all in an engaging, easy-to-apply manner"- Resumé vydavatel
Keywords: uživatelská rozhraní; WWW design; interakce člověk-počítač; informační architektura; ergonomie; užitkový design; user interfaces; human-computer interaction; information architecture; human engineering; design for use; elektronické knihy; příručky; electronic books; handbooks and manuals